Public policy training in Latin America: Current status and challenges for political science - Nicolás Bentancur; Germán Bidegain; Rodrigo Martínez (Íconos)
The present article analyzes training in public policy at the undergraduate level in Political Science programs at 11 Latin American countries. This research addresses the profile of instructors, the most often quoted authors and texts and the importance granted to knowledge produced both inside and outside the region. The examination of 109 syllabi from 69 universities can detect the incidence of significantly different training backgrounds among instructors. In some cases locally obtained degrees prevail, while in other cases, foreign training is predominant. This has a direct impact in the relative prominence granted to either domestic or external sources in course reading lists. The article is able to establish that – in spite of recent progress- the use of references taken from texts produced within the region is still limited. In all countries -although in a different degree in each case- , the process of building a “science of policy” is hampered by the straightforward and indiscriminating adaptation of theoretical models and frameworks originally produced in and for countries in the developed world, as well as for the still scarce referencing of local intellectual production and/or of Latin American sources. This, in turn, obstructs a meaningful dialogue with the most influential international intellectual production and hinders future prospects for homegrown research able to account for specific national and regional experiences and dynamics.